The Running Track of Government Responsibility During the Pandemic, Characteristic Analysis of Policy Documents Relevant to the COVID-19 Pandemic Released by Beijing Municipal Government in 2020 - Mao, Ayan; Yang, Yujie; Qiu, Wuqi (Frontiers in Public Health, 2021)
Objective: Provide a reference point for the division of labor during the collaboration of multiple departments and the planning for the prevention and control of the Covid-19 epidemic of departments of the Beijing Municipal Government, from the perspective of policy documents. Methods: Policy documents and daily updates on COVID-19 cases published in 2020 are taken from the official website of Beijing Municipal Government and Beijing Municipal Health Commission. The characteristics of the pandemic situation and the content of relevant documents issued by different departments are described in five stages. Results: There were 988 confirmed cases of COVID-19 in Beijing in 2020, and policy analysis covered 444 documents (257 policy documents and 187 explanations of policy). A total of 153 policy documents were directly issued by the Beijing Municipal Government and its 45 subordinate commissions and bureaus, while others were policy forwarding from the central government and its relevant departments, county-level governments of Beijing and other organizations. Most cases and documents emerged during the initial stage of the pandemic (Level-I of the Emergency Response, which is the most serious). It was found that as many as 109 documents published by Beijing Municipal Government during the Level I emergency response period were relevant to economic and social development, 83 documents were related to disease control and medical services, and the rest were in close relation to the production and daily life of the people. Overall, major policy measures taken were relevant to 7 fields: finance, transportation, economic activities, employment people's lives, epidemic prevention and control and medical insurance. Policy implementation objectives were centered on promoting epidemic prevention and control and maintaining the stability of social production and residents' life. However, there are different emphases in different stages of the epidemic. Conclusion: Beijing municipality realized an effective mode of collaboration among multiple departments and organizations in the prevention and control of the COVID-19 epidemic, which was an example of the practice of “Health in All Policies.”